2012
DOI: 10.1186/1297-9716-43-21
|View full text |Cite
|
Sign up to set email alerts
|

Stress significantly increases mortality following a secondary bacterial respiratory infection

Abstract: A variety of mechanisms contribute to the viral-bacterial synergy which results in fatal secondary bacterial respiratory infections. Epidemiological investigations have implicated physical and psychological stressors as factors contributing to the incidence and severity of respiratory infections and psychological stress alters host responses to experimental viral respiratory infections. The effect of stress on secondary bacterial respiratory infections has not, however, been investigated. A natural model of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 42 publications
3
36
0
1
Order By: Relevance
“…5 The earliest studies demonstrated associations between naturally occurring stressors and telomere biology in noncancer samples, in which stress was associated with shorter TL and lower telomerase activity. 15,16 Although stress plays a role in the etiology and progression of many diseases, [17][18][19] the role of stress in cancer remains suggestive. 20,21 Nonetheless, several biobehavioral pathways between psychosocial stress and mechanisms of cancer development have been indentified.…”
Section: Introductionmentioning
confidence: 99%
“…5 The earliest studies demonstrated associations between naturally occurring stressors and telomere biology in noncancer samples, in which stress was associated with shorter TL and lower telomerase activity. 15,16 Although stress plays a role in the etiology and progression of many diseases, [17][18][19] the role of stress in cancer remains suggestive. 20,21 Nonetheless, several biobehavioral pathways between psychosocial stress and mechanisms of cancer development have been indentified.…”
Section: Introductionmentioning
confidence: 99%
“…Stress induced by abrupt weaning, maternal separation and transportation of suckled beef calves alters the immune response and increases susceptibility to fatal bovine respiratory disease (Hodgson et al, 2012). Our group has previously reported that abrupt weaning exerts an acute stress response in single-suckled beef calves, characterised by changes in the distribution of haematological cells (Lynch et al, 2010;O'Loughlin et al, 2011) and up-regulation in expression of genes involved in the pro-inflammatory response (O'Loughlin et al, 2011).…”
mentioning
confidence: 99%
“…Psychological stress results in the enhanced production of corticosteroids and catecholamines [21] which are potent immunomodulators [22]. In animal models, high-stress environments have been associated with increased morbidity and mortality following bacterial and viral infection [23,24]. People experiencing stressful life events, such as marital problems or caring for a sick relative, have been shown to have altered immunity such as a lower antibody response to influenza vaccination [25] and reactivation of latent viral infections [26].…”
Section: Introductionmentioning
confidence: 99%